Layanan Komunikasi Ilmiah (Scholarly Communication Services) Direktorat Perpustakaan Universitas Islam Indonesia Dalam Mendukung Penelitian Civitas Akademika - Rheza Ega Winastwan, Rheza; Syarif, Fatimah Azhar (Universitas Islam Negeri Salatiga, 2025)
In this study, the researcher used a qualitative method with a case study approach. Data collection was obtained through library studies, interviews, and documentation. The Scholarly Communication service at the Library Directorate of the Islamic University of Indonesia (UII) Yogyakarta is one of the services that bridges the academic community related to research activities. This service helps students and lecturers in supporting research activities. The manifestation of these services includes determining research ideas or topics, providing software for reference management, and helping academic communities access information sources as publication media.